NFC Enabled E-Services for Employees - Sowmya, P.; Banu Priya, N. (Asian Journal of Electrical Sciences, 2015)
This project establish a easy shopping for the employees through their smart phones. Whenever they went shop they can pay the Bill through this mobile application. Also the employees in companies pay their transport charges through mobile phone with NFC technology. The application installed in the phone has been paired with the RASBERRY-PI Controller through BLUETOOTH. Already thriving within the telecommunications market, wireless technology is preparing to embrace computing on an even larger scale. Presently, most people encounter wireless local area networks (WLANs) in airport lounges and tech-savvy offices. Everywhere around the world, this new generation prefers the wireless technology for their work and also the technologies are growing by leaps and bound to carry out all the desires of the customers to fulfill their demands. Here we use that wireless technology into the on chip computer (raspberry PI). We are going to implement multiple applications in a single unit. From this we can learn how embedded units are flexible with real time applications. In our project we use two concepts. First one is E-vouchers for employees second one is a E-ticket system all are done with the help of Near field communication (Bluetooth) technology.